Ricardo Reis e o mundo : o poeta das Odes e a personagem de O ano da morte de Ricardo Reis - Massucato, Anamélia Rodrigues Marquis (2006)
During the 20th century, the Portuguese society underwent many transformations. The first years brought new cultural and aesthetic perspectives, which had slowly been generated during the previous century, and that, at least, emerged. Fernando Pessoa's poetry reflects any way these transformations that was started in the 19th century, which resulted into the dramatic play of heteronyms present in his poetry, requiring the reader to re-create the way gone through. This dissertation aims to verify, by reading Fernando Pessoa's Odes, how the heteronymous Ricardo Reis relates to the world, and compares this position to that one adopted by the main character from the novel O Ano da Morte de Ricardo Reis, published in 1984, written by José Saramago. The research is based on reading and reporting theoretical, critical and analytical texts, and adopts the reader-response criticism postulated by Hans Robert Jauss and Wolfgang Iser, as well as on the thematic and stylistic analyses of Ricardo Reis' Odes and of the novel O Ano da Morte de Ricardo Reis, by José Saramago. The research is justified by the verification of a possible contradiction between the heteronymic creation and the re-creation of the character in the novel, making possible an overture for the comparison between the "mask" present in the Odes and the re-creation made by Saramago, focusing the mode how the poet and character place themselves and act towards the reality that surround them. In other words, the research intends to verify if the image emanated from the verses in Odes correspond to the novel character erected from the reading done by Saramago of Pessoa's heteronym concerning to the relation of the man with the world. Firstly, it is presented data and information about the Modernism in Portugal and the context in which this movement was inserted. Secondly, follows a study on Fernando Pessoa and the question of heteronym, remarkable fact for his work; finally, this work reaches its highest point with the analysis of the Ricardo Reis-heteronym and the main character in the novel, filling the gaps and trying to make emerge the different visions of the world and his relation with it. The aspects verified, from the reading of the intertextualities, refer to the difficulties, joys, pleasures, love, women, nature, politics, and death, at last, all that refers to the daily life, taking into account that between the reader and the ideas propagated is interposed the text and that it is open to diverse possibilities of reading realizations, in conformity to the different perspectives from those who seek for it.